KINERJA DAN KOMPETENSI GURU DALAM PEMBELAJARAN - Muh. Ilyas Ismail (Lembaga Pendidikan dan Tenaga Kependidikan (Center for Teacher Training) Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar in collaboration with Lecturer Consortium of Tarbiyah and Teacher Training, 2010)
The performance and competence of a teacher has been an important point to discuss due to the fact that it can be a legal aspect in designing and developing performance and competence of teachers. Performance is the extent to which a teacher has achieved in terms of working responsibility, in other word, a teacher's working achievement. Hence, teachers with high performance are those who master teaching material and the method of teaching. Teacher's performance can be assessed by three indicators: the mastery of teaching material, teaching management, and working commitment. While the teacher's competences based on the Constitution number 14/2005 are pedagogic competence, personal, social and professional competence.